Comfy cozy

Geometry Level 5

Let R R be the region in the first quadrant that is

(i) inside the circle x 2 + ( y 3 ) 2 = 9 x^{2} + (y - 3)^{2} = 9 , and

(ii) outside the circles x 2 + ( y 2 ) 2 = 4 x^{2} + (y - 2)^{2} = 4 and x 2 + ( y 5 ) 2 = 1 x^{2} + (y - 5)^{2} = 1 .

(The boundary lines of R R are included as part of the region.)

The largest circle that can be inscribed in R R has radius r = a b r = \dfrac{a}{b} , where a a and b b are positive coprime integers. Find a + b a + b .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let A , B , C , D A, B, C, D be the respective centers of the radius 2 , 3 , 1 , r 2, 3, 1, r circles.

Then A B = 1 , B C = 2 , A D = 2 + r , B D = 3 r AB = 1, BC = 2, AD = 2 + r, BD = 3 - r and C D = 1 + r CD = 1 + r .

Let A B D = x \angle ABD = x ; then C B D = π x \angle CBD = \pi - x .

Now use the Cosine Law on triangles A B D ABD and C B D CBD to find that

(i) ( 2 + r ) 2 = 1 + ( 3 r ) 2 2 ( 3 r ) cos ( x ) (2 + r)^{2} = 1 + (3 - r)^{2} - 2*(3 - r)*\cos(x) and

(ii) ( 1 + r ) 2 = 4 + ( 3 r ) 2 + 4 ( 3 r ) cos ( x ) (1 + r)^{2} = 4 + (3 - r)^{2} + 4*(3 - r)*\cos(x) .

Multiply equation (i) by 2 2 and add to equation (ii) and simplify to find that r = 6 7 r = \dfrac{6}{7} .

Thus a = 6 , b = 7 a = 6, b = 7 and a + b = 13 a + b = \boxed{13} .

Simply awesome!

Pranjal Jain - 6 years, 7 months ago

Log in to reply

Thanks, Pranjal. :)

Brian Charlesworth - 6 years, 7 months ago

Alternately , use Heron's formula and state that area(BCD) = area(ABD) *2 ... for both triangles , s = 3.

Rajnish Singh - 6 years, 3 months ago
Abhishek Singh
Nov 7, 2014

Obviously the largest circle should be tangent to all the other three circles which are given hence by Descartes'rule we can solve for the curvature of the circle and finally it's radius.Here we go ( k 1 + k 2 + k 3 + k 4 ) 2 = 2 ( k 1 2 + k 2 2 + k 3 2 + k 4 2 ) (k_1 +k_2+k_3+k_4)^2= 2({k_1}^2+{k_2}^2+{k_3}^2+{k_4}^2) where k 1 = 1 3 a n d k 2 = 1 2 k 3 = 1 k 4 = x k_1=-\dfrac{1}{3} and \quad k_2=\dfrac{1}{2}\quad k_3=1\quad k_4=x where k is the curvature i.e. reciporcal of the radius of the circles pluging in these values and after solving we get r = 6 7 r=\boxed{\dfrac{6}{7}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...